Correction of refractive error in the Victorian population: the feasibility of "off the shelf" spectacles. Issue 11 (1st November 2001) - Maini, Raj; Keeffe, Jill; Weih, Le Ann; McCarty, Catherine A; Taylor, Hugh R
Abstract : AIMS: To assess the feasibility of providing a stock of ready made spectacles for correction of refractive error in the general population. METHODS: Data were collected in the Visual Impairment Project, a population based survey of Victorian residents aged 40 years or older in randomly selected urban and rural sample areas. This included a refractive eye examination and the proportion of subjects with hypermetropia, emmetropia (defined as −1.0 to +1.0D spherical equivalent), and myopia documented in the 40–60 year age group. RESULTS: 2595 (54.8%) participants were aged between 40 and 60 years. Those with a best corrected visual acuity of less than 6/12, astigmatism of more than 1.25D, and anisometropia of more than 0.5D were excluded. 516 participants had refractive error which was deemed suitable for correction by "off the shelf" spectacles. This represents 19.9% of all participants between 40 and 60 years of age. Provision of spectacles in 0.5D increments would provide suitable stock spectacles for 85.5% of a −3.0 to +3.0D range or 89.2% of a −3.50 to +3.50D range. CONCLUSIONS: Ready made "off the shelf" spectacles could significantly alleviate visual morbidity due to refractive error in up to 20% of an urban population in Australia. This approach may also be useful in developing countries with poor access to optometric services.